Histological characteristic of destructive changes in the shoulder joint at arthrosis model - Sergienko, Ruslan; Strafun, Sergiy; Savosko, Sergiy; Makarenko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Late treatment of shoulder joint arthrosis and insufficient assessment of pathogenetic components in the appearance and progression of pathological changes in the cartilage lead to the rapid progression of the disease. Traumatic damage of the joint capsule-ligamentous apparatus and impaired mobility are considered one of the main factors for the development of this pathology. But the disturbance of the shoulder joint biomechanics as a factor in the development of arthrosis remains not fully understood. Objective: to study the dynamics of structural changes in the articular surface of the humerus head in the guinea pigs model, when we reproduced the disturbance of biomechanics and the formation of shoulder joint contracture. Methods: the experiments were carried out on guinea pigs weighing 380–420 g, 5 months old. Reproduced model of surgical limitation of joint mobility, which caused the formation of contracture. Histology and scanning electron microscopy examined the condition of the articular cartilage and subchondral bone after 30, 60 and 90 days after modeling. Results: 30 days after surgery in the articular cartilage, degenerative changes were detected, which progressed with the formation of a joint contracture by the 90th day of observation. Destructive changes in articular cartilage after 60 days were manifested by the destruction of its superficial zone, disturbances in the structure of the matrix and chondrocytes, which led to sclerosis of the subchondral layer after 60 and 90 days. The obtained data confirmed the hypothesis that impaired biomechanics and abnormal loads are an independent factor in the development of arthrosis of the shoulder joint. The most critical period was from 30 up to 60 days. Conclusions: the first 30 days after the disturbance of the biomechanics of the shoulder joint can be considered as a therapeutic window for the medical and functional correction of the pathological process.